Abstract 123: First Off‐Label Use of the XIENCE Skypoint Stent for Mechanical Thrombectomy Rescue - Noor A Mahmoud (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Despite technical advances in mechanical thrombectomy (MT), failure to achieve recanalization in the posterior circulation remains a significant challenge. Rescue strategies to increase MT success in the posterior circulation have been explored. We demonstrate the first successful off‐label use of XIENCE Skypoint™ (Abbott), a balloon‐mounted drug‐eluting stent (DES), for intracranial MT rescue in the posterior circulation. Methods Case report and endovascular technique. Results A 52‐year‐old man with hypertension, hyperlipidemia, and deep venous thrombosis who presented with acute ischemic stroke in bilateral occipital, lateral pons, and cerebellar regions. Computed tomography angiography (CTA) showed bilateral vertebral artery occlusion consistent with a history of dissection in the setting of cervical manipulation. Admission National Institutes of Health Stroke Scale (NIHSS) 20. Last known well less than 12 hours from presentation. Intravenous thrombolysis was deferred as the patient was on pre‐admission anticoagulants. Mechanical thrombectomy failed after several unsuccessful passes (Fig 1). XIENCE Skypoint™ stent was deployed within the left vertebral artery (V4 segment) with restoration of flow preceded by eptifibatide drip (Fig 2). Repeat CTA at six months showed patent left vertebral and basilar arteries. Conclusion Rescue stenting using DES may be a successful and safe therapeutic intervention for challenging failed MT. The off‐label use of DES for intracranial pathologies continues to expand. This is the first case report in the literature describing successful rescue stenting using XIENCE Skypoint™ in the posterior circulation. Further investigation is warranted to fully elucidate the risks and benefits of this treatment approach.